2016
DOI: 10.1186/s12875-016-0542-8
|View full text |Cite
|
Sign up to set email alerts
|

Safer drug use in primary care - a pilot intervention study to identify improvement needs and make agreements for change in five Swedish primary care units

Abstract: BackgroundThere is an urgent need to improve patient safety in the area of medication treatment among the elderly. The aim of this study was to explore which improvement needs and strengths, relating to medication safety, arise from a multi-professional intervention in primary care and further to describe and follow up on the agreements for change that were established within the intervention.MethodsThe SÄKLÄK project was a multi-professional intervention in primary care consisting of self-assessment, peer-rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Relevant information was sought via different sources, such as by gaining access to the hospital medical electronic records not normally accessible to the GPs, clearly suggesting failure of the information transfer. Indeed, common medical records is often viewed as a way to improve communication [ 4 , 31 ], but must be kept accurate to be of value [ 4 , 37 ]. A common medical record and medication list was also a general wish for the future in our study, which however does not eliminate the responsibility to work for well-functioning care transitions in the meantime.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant information was sought via different sources, such as by gaining access to the hospital medical electronic records not normally accessible to the GPs, clearly suggesting failure of the information transfer. Indeed, common medical records is often viewed as a way to improve communication [ 4 , 31 ], but must be kept accurate to be of value [ 4 , 37 ]. A common medical record and medication list was also a general wish for the future in our study, which however does not eliminate the responsibility to work for well-functioning care transitions in the meantime.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, a recent study from the Netherlands showed one third of in-hospital prescription changes was not or incorrectly documented in the primary care medical record [ 33 ], which is in line with a previous study on post-discharge medication-related information [ 34 ]. According to previous Swedish and American studies, discrepancies between the patients’ intended medication regimen and the medication list in primary care are common [ 35 – 37 ], even with a common medical record [ 35 , 36 ], and the need for great improvement regarding updated medication lists was noted [ 38 ]. An accurate medication list is essential to assess the patient’s symptoms as well as the risks and effects of treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common medication list for hospital and primary care was also proposed in the survey free text comments. Even though a common list could increase medication safety, this may fail due to unsatisfactory maintenance and frequent errors [ 35 , 38 ]. In addition, hoping for a future common list does not eliminate the responsibility to keep current medication lists accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This project was multi‐professional and involved six professional health care organizations with the aim to determine whether an intervention could improve drug safety in elderly patients . The outcome of the project showed promising results . A second project, SÄKLÄK2, was initiated in 2016 in order to further assess the effect of the intervention model and to evaluate the possibility to introduce this model more widely across Sweden.…”
Section: Introductionmentioning
confidence: 99%